End of treatment and 12-month post-treatment outcomes in patients treated with all-oral regimens for rifampicin-resistant tuberculosis in Ukraine: a prospective cohort study. - Vini Fardhdiani; Olena Trush; Nataliia Lytvynenko; Svitlana Pylypchuk; Yana Terleeva; Khachatur Malakyan; Praharshinie Rupasinghe; Yves Wally; Marve Duka; Vitaly Stephanovich Didyk; Olga Valentinovna Siomak; Oleksandr Blyzniuk; et al. (PLOS Global Public Health)
The World Health Organization has called for operational research on all-oral shorter regimens for rifampin-resistant and multidrug-resistant forms of tuberculosis (RR/MDR-TB). We followed a cohort of patients in Zhytomyr, Ukraine for effectiveness, safety, tolerability and feasibility of bedaquiline & delamanid-based treatment regimens under programmatic conditions. This was a single-arm implementation study. All consenting persons with RR/MDR-TB were enrolled between 1 April 2019 and 31 May 2021 and followed up 12-months after treatment completion. We assessed quality of life and depression symptoms between start and end-of-treatment. We enrolled 300 patients. Overall, 212 (71%) patients were cured, 22 (7%) patients completed treatment, median time to culture conversion was 58 days (IQR:30-75), and 21% and 27% of patients had at least one serious or Grade 3/4 adverse event, respectively. The overall BREF-WHO/Quality of Life score improved between baseline and end-of-treatment, from average 52.64(std. dev:21.63) to 57.15(std. dev:21.43) while Patient Health Questionnaire-9(PHQ-9) score decreased from 6.67(std. dev:4.75) at baseline to 5.34(std. dev: 5.18) at end-of-treatment. Twelve months post-treatment 174/234(74%) were alive and recurrence-free, 17(7%) patients died, one (<1%) had recurrent TB, while 42 (18%) were lost from the post-treatment follow-up. All-oral short-term regimens showed high success under programmatic conditions in Ukraine, despite extreme implementation challenges during the COVID-pandemic and the Russia-Ukraine war. Moreover, this was a cohort of patients with high levels of co-morbidities and substance use. A multidisciplinary, psychosocial support model might have contributed to satisfactory treatment outcomes, improved quality of life and decreased symptoms of depression among people living with RR/MDR-TB.